Nonleukemic Ureteral Granulocytic Sarcoma Presenting with Unilateral Urinary Obstruction and Hematuria - Ömer Acar; Tarık Esen; Tülay Tecimer; Mustafa Çetiner; Önder Peker; Ahmet Musaoğlu (Case Reports in Urology)
Granulocytic sarcoma is an extramedullary tumor which is composed of myeloblasts and immature myeloid cells. It usually occurs in association with acute myeloid leukemia and most commonly involves skin, soft tissue, lymph nodes, bone, and periosteum. We report a case of isolated ureteral granulocytic sarcoma without hematologic manifestations. Our patient presented with bloody urine and left-sided lumbar pain. Preoperative clinical and radiologic features raised the suspicion of an upper urinary tract transitional cell carcinoma, and he was scheduled for nephroureterectomy. However, perioperative pathologic feedback and the unusual endoscopic appearance of the tumor altered our surgical strategy towards segmental ureterectomy and ureteroneocystostomy. Eventual pathologic diagnosis was granulocytic sarcoma of the ureter. Postoperative workup failed to demonstrate any sign of an accompanying hematologic disorder. He started receiving the chemotherapy protocol of acute myeloblastic leukemia. To our knowledge, this is the first documented case of nonleukemic ureteral granulocytic sarcoma which came to attention due to urologic complaints.